The maximal cumulative solar UVB dose allowed to maintain healthy and young skin and prevent premature photoaging. (October 2014) - Ichihashi, Masamitsu; Ando, Hideya
Abstract: The young facial skin of children with a smooth healthy appearance changes over time to photoaged skin having mottled pigmentation, solar lentigines, wrinkles, dry and rough skin, leathery texture, and benign and malignant tumors after exposure to chronic, repeated solar radiation. The first sign of photoaging in Japanese subjects is usually solar lentigines appearing around 20 years of age on the face. Fine wrinkles can then appear after 30 years of age, and benign skin tumors, seborrhoeic keratoses, can occur after 35 years of age in sun‐exposed skin. We theoretically calculated the maximal daily exposure time to solar radiation, which could prevent the development of photoaged skin until 60 and 80 years of age, based on published data of personal solar UVB doses in sun‐exposed skin. One MED (minimal erythema dose) was determined to be 20 mJ/cm 2, and 200 MED was used as the average yearly dose of Japanese children. Further, we hypothesized that the annual dose of Japanese adults is the same as that of the children. The cumulative UVB dose at 20 years of age was thus calculated to be 4000 MED, and 22 MED was used as the maximal daily UVB dose based on data measured in Kobe, located in the central area of Japan. We used the solar UVB dose from 10:00 a.m. to 14:00 p.m. which occupies 60% of the total daily UV dose, to obtain the maximal UVB per hour in a day, and calculated the maximal daily UV exposure time that would delay the onset of solar lentigines until 60 or 80 years of age. The mean daily sun exposure time to maintain healthy skin until 80 years of age in the summer was calculated to be 2.54 min (0.14 MED) for unprotected skin and 127 min with the use of a sunscreen of SPF (sun protection factor) of 50. In this study, we did not evaluate the photoaging effect of UVA radiation, but findings of the adverse effects of UVA radiation on the skin have accumulated in the last decade. Therefore, it will be important to estimate the maximal dose of solar UV radiation to retard the onset of photoaging based on an evaluation of both solar UVB and UVA in the future. Finally, we expect that this study may contribute to keeping Japanese and other types of skin young and healthy by limiting the exposure of the skin to solar radiation outdoors during the day.